2022
DOI: 10.1021/acsbiomaterials.2c01284
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion Complexation of S-Nitrosoglutathione for Sustained Nitric Oxide Release from Catheter Surfaces: A Strategy to Prevent and Treat Device-Associated Infections

Abstract: S-Nitrosoglutathione (GSNO) is a nontoxic nitric oxide (NO)-donating compound that occurs naturally in the human body. The use of GSNO to deliver exogenous NO for therapeutic and protective applications is limited by the high lability of dissolved GSNO in aqueous formulations. In this paper, we report a host−guest chemistry-based strategy to modulate the GSNO reactivity and NO release kinetics for the design of antiinfective catheters and hydrogels. Cyclodextrins (CDs) are host molecules that are typically use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…The NO release levels obtained in these SNAPicillin studies were found to be lower compared to previously reported studies comprising of the less bulky and hydrophilic SNACET, GSNO, and GSNO-cyclodextrin-based NO-releasing lock solutions. 14,15,31 However, the high NO release levels seen from these previously reported studies can be attributed to the higher concentrations of solutions utilized (as high as 100 mM) compared to 10 mM concentration of SNAPicillin used in this study. Although the NO release levels from the SNAPicillin solution were observed to be lower, the antibacterial efficiency of SNAPicillin is noted to be the most efficient with 4.28 and 8.24 log reductions in S. marcescens and E. coli bacteria due to the synergy with the covalently bound ampicillin, respectively, when compared to previously reported NO-releasing lock solutions.…”
Section: Resultsmentioning
confidence: 71%
“…The NO release levels obtained in these SNAPicillin studies were found to be lower compared to previously reported studies comprising of the less bulky and hydrophilic SNACET, GSNO, and GSNO-cyclodextrin-based NO-releasing lock solutions. 14,15,31 However, the high NO release levels seen from these previously reported studies can be attributed to the higher concentrations of solutions utilized (as high as 100 mM) compared to 10 mM concentration of SNAPicillin used in this study. Although the NO release levels from the SNAPicillin solution were observed to be lower, the antibacterial efficiency of SNAPicillin is noted to be the most efficient with 4.28 and 8.24 log reductions in S. marcescens and E. coli bacteria due to the synergy with the covalently bound ampicillin, respectively, when compared to previously reported NO-releasing lock solutions.…”
Section: Resultsmentioning
confidence: 71%
“…[1][2][3][4]. При этом важно отметить крайне малое время жизни молекулы монооксида азота, составляющее в среднем 6 секунд в свободном состоянии [5,6], что предъявляет высокие требования к регуляции метаболизма данного соединения и обеспечивает необходимость присутствия в организме веществ, временно депонирующих NO либо создающих условия для его синтеза в случае необходимости [7,8].…”
Section: Introductionunclassified